The Effect of Key Operating Conditions on Grinding Media Consumption in Semiautogenous Mills - Levi Guzmán Rivera; Sepulvedam Jaime E. (Canadian Institute of Mining, Metallurgy and Petroleum, 2016)
"Grinding media consumption rates and their dependence on key operating conditions in semiautogenous grinding mills is analyzed on the basis of a detailed mathematical model recently developed by Moly-Cop´s specialists which describes and takes into account the three primary media consumption mechanisms, namely: abrasion/corrosion, surface spalling and impact ball breakage. The influence of key mill operating conditions – such as ball filling, discharge grate opening, mill speed, lifter profile, and ball quality – on their corresponding grinding media consumption rates is explored via a variety of model simulations, discussing in every case the independent contribution of each of the indicated consumption mechanisms to the estimated total ball consumption rate.INTRODUCTIONA thorough understanding of the independent contribution of each grinding media wear mechanism is extremely important, especially in semi-autogenous grinding (SAG) operations where macrowear (spalling) and ball breakage cannot be ignored or neglected. The high impact conditions imposed in modern SAG milling environments has created serious challenges for grinding media manufacturers since their products must be able to perform with minimal breakage and surface spalling.GRINDING MEDIA WEAR MECHANISMFor SAG milling operations, at least 3 different mechanisms have been identified as the main contributors to the observed overall grinding media consumption, here referred to as: abrasion / corrosion, ball breakage and surface spalling.Wear by Abrasion/CorrosionThe abrasive/corrosive wear mechanism has been discussed in depth in previous publications (Benavente Hector, 2007; Guzman Levi, 2014; Sepulveda and Morrow, 2014). The most widely accepted approach to mathematically characterize the consumption (wear) kinetics of grinding media in rotary tumbling mills is known as the Linear Wear Theory (Prentice, 1943; Norquist, 1950; Sepulveda, 2004) which claims that—at each instant 't' after a grinding body enters the mill load—the rate at which the body loses weight is directly proportional to its surface area exposed."